Peningkatan Literasi Digital Siswa SMKN 1 Kota Bengkulu Melalui Pelatihan Ai For Beginners Untuk Mendorong Kreativitas Dan Inovasi Teknologi - Putri, Sandrina Zahra; Ronaldi, Ahmad; Aprilia, Alfarida Dewi; Rostita, Levi Oga; Akbar, Andika Tresna Hariadi; Rozzi, yoli Andi (Jurnal Gotong Royong, 2026)
This study aims to describe the efforts to improve digital literacy among students of SMKN 1 Kota Bengkulu through the “AI for Beginners” training program. The rapid development of artificial intelligence requires students to understand basic technological concepts to encourage creativity and innovation. This research uses a descriptive qualitative method involving approximately 60–65 vocational school students as participants. Data were obtained through observation during training activities, informal interviews, and documentation. The results show that students were highly enthusiastic and responded positively to the presence of the training team. They showed strong motivation to learn and explore artificial intelligence, although their understanding of the material was limited due to the English-based training content. Nevertheless, the activity successfully introduced AI fundamentals and stimulated students’ interest in further learning. This program is expected to be a foundation for more structured digital literacy development in vocational schools.